Access to 8-Aminoindolizine Fused with Quinone via Cu(OAc)2-Catalyzed Domino [4+2] Annulation - Lee, Sunhee; Lee, Yechan; Namkung, Wan; Kim, Ikyon (Synthesis, 2024)
Cu(OAc)2-catalyzed [4+2] annulation of N-substituted pyrrole-2-carbonitriles with quinones allowed access to a wide range of 8-aminoindolizines fused with quinones through a domino process involving a sequence of intermolecular Michael addition, Thorpe–Ziegler type cyclization, and aromatization. Biological evaluation of the resulting quinone-8-aminoindolizine hybrids revealed significant anticancer effects of these compounds in human hepatocellular cells (HepG2) and prostate adenocarcinoma cells (PC-3).
Keywords: chemical space; quinone; indolizine; hybrid structure; domino reaction; diversity-oriented synthesis; atom-economy; anticancer activity